The Effect of Employer Branding on Employee Retention of Technical Support Employees in Internet Service Provider (ISP) Companies (ION Network Case Study) - Giovanni, Jane; Dwianto, Agung Surya (SAFE-Network, 2025)
This study explores the influence of employer branding on employee retention among Technical Support staff at ION Network, a leading Internet Service Provider (ISP) in Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and company document analysis. The study involved three key informants: a Technical Support employee, the Vice President of Technical Support, and an HRD specialist. The findings reveal that ION Network’s employer branding anchored in national project participation, practical technical training, and family focused benefits fosters emotional and professional engagement, thereby enhancing employee loyalty. Training initiatives and public recognition of high performing staff further strengthen job satisfaction. However, the study also highlights retention challenges, particularly the gap between the hierarchical structure and the high mobility expectations of young employees, as well as salary competition from rival firms. These challenges indicate the need for more adaptive branding strategies that align with generational preferences and market dynamics. The study concludes that employer branding at ION Network operates as both a recruitment and retention tool, effectively combining external corporate image with internal employee value. The implications underscore the importance of purpose driven work environments, continuous learning systems, and flexible career pathways in maintaining a stable and committed workforce in the ISP sector.